2011
DOI: 10.1111/j.1365-2664.2010.01948.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation management of eastern Australian farmland birds in relation to landscape gradients

Abstract: Summary1. Birds inhabiting farmland are of conservation concern around the world. In Australia, conservation management has focused primarily on woodland environments. By contrast, semi-natural open areas have received less attention. We argue that long-term conservation strategies should consider broad gradients of environmental conditions. Otherwise, there is a risk that semi-natural open areas will degrade through 'benign neglect', and currently common species using these areas will become uncommon. 2. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…Because birds were the main sunflower seed predators in our study area, our results agree with the findings of Hanspach et al (2011) who found that scattered trees were key habitat structures for birds in semi-natural open areas. We observed flocks of a few hundreds of birds of the Rose-Ringed Parakeet in our study area, (Personal Observation and reports by local farmers) (Figure 1), one of the main bird pests to agriculture in Israel (Nemtzov, 2003).…”
Section: Discussion High Trees Adjacent To Crop Fields and Seed Predasupporting
confidence: 83%
“…Because birds were the main sunflower seed predators in our study area, our results agree with the findings of Hanspach et al (2011) who found that scattered trees were key habitat structures for birds in semi-natural open areas. We observed flocks of a few hundreds of birds of the Rose-Ringed Parakeet in our study area, (Personal Observation and reports by local farmers) (Figure 1), one of the main bird pests to agriculture in Israel (Nemtzov, 2003).…”
Section: Discussion High Trees Adjacent To Crop Fields and Seed Predasupporting
confidence: 83%
“…Overall, the diet of species might be a relevant trait to explain species assortment in intensive agriculture. However, the species trophic category (STI) was not involved in the beta diversity decline, suggesting that species replacement, and/or dissimilarities derived from nestedness, do not depend on the species position within the trophic network but maybe rather on the vegetation layer of foraging (Hanspach et al, 2011). By extension, all trophic levels can be affected by agricultural intensification.…”
Section: Explaining Taxonomic Responses By Species' Ecological Traitsmentioning
confidence: 92%
“…Similarly, a Community Trophic Index (CTI), adapted from the Marine Trophic Index (Pauly and Watson, 2005), has been proposed as a surrogate of the potential trophic complexity within bird communities (Jiguet et al, 2012). This index has not yet been tested in agricultural landscapes, though these have been shown to favour granivorous and ground insectivorous species, leading to less diversified diet composition in farmland than in forested areas (Hanspach et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fire is an important driver of the occurrence of birds in Australian woodlands and forests, given its influence on the age and structure of vegetation Burgess & Maron, 2015;Haslem et al, 2016). Scattered paddock trees (Fischer et al, 2010b;Hanspach et al, 2011), and regrowth vegetation (Bowen et al, 2009b;Smallbone et al, 2014) have also been shown to affect the spatial composition of bird communities, due to the habitat resources they provide as a complement to remnant native vegetation.…”
Section: Key Implications For Applied Landscape Management 622mentioning
confidence: 99%